Ogólne Zasady Mechanicznej Interpretacji Macierzowej. Metody Obliczania Systemów Prętowych. - Ponomariew, K.K. (Engineering Transactions, 1964)
This paper contains general principles of computation of systems composed of bars and beams by means of the matrix method. The problems discussed are those of bending, stability and vibration of a system, The method proposed enables the application of modern computation methods and electronic computers.